Viral Interactions with Host RNA Decay Pathways - Karen L. Beemon (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Eukaryotes have evolved a wide variety of RNA decay pathways to maintain cellular homeostasis, carry out programs of gene expression, and respond to changing environmental conditions. Individual RNA turnover mechanisms can operate constitutively or under only particular cellular conditions; similarly, some target many RNAs, while others act with great specificity. It has become increasingly clear that there are extensive interactions between viruses and the host RNA decay machinery. Often, the cellular RNA decay machinery poses a threat to viral gene expression, but viruses can also manipulate RNA decay pathways to promote viral replication. This special issue focuses on how cellular RNA decay factors recognize and degrade viral RNAs and viral strategies to subvert or evade these pathways.